2014
DOI: 10.1007/s00403-014-1470-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of nuclear factor E2-related factor 2 (Nrf2) in epidermal differentiation

Abstract: Nuclear factor E2-related factor 2 (Nrf2) is one of the most important redox-sensitive transcription factors regulating expression of antioxidative genes and cytoprotective enzymes, which constitute the cellular response to oxidative stress and xenobiotic damage. In this study, we investigated the functional role of Nrf2 during normal epidermal keratinocyte (NHEK) differentiation. Immunohistochemical staining showed that Nrf2 is expressed from basal to granular layer of epidermis. When cultured NHEKs were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…We explored the possible mechanisms underlying these effects. Since Nrf2 has recently been mentioned as an important regulator of the oxidative response as well as of differentiation of keratinocytes (Beyer, et al, 2007;Lee, et al, 2014), we determined whether MMF increased Nrf2 levels by using a 200 mM concentration of MMF as was done in several other systems (Nibbering, et al, 1993;Thio, et al, 1994;Garcia-Caballero et al, 2011), as well as a 300 mM dose that we had previously shown to inhibit inflammatory mediator production in keratinocytes (Helwa et al, 2015). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We explored the possible mechanisms underlying these effects. Since Nrf2 has recently been mentioned as an important regulator of the oxidative response as well as of differentiation of keratinocytes (Beyer, et al, 2007;Lee, et al, 2014), we determined whether MMF increased Nrf2 levels by using a 200 mM concentration of MMF as was done in several other systems (Nibbering, et al, 1993;Thio, et al, 1994;Garcia-Caballero et al, 2011), as well as a 300 mM dose that we had previously shown to inhibit inflammatory mediator production in keratinocytes (Helwa et al, 2015). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nrf2 has two effects, firstly, promotes regeneration and expression of antioxidant enzymes [61], and secondly, it can perpetuate the survival of damaged cells by ROS generated during aerobic metabolism, and the respiratory burst of the immune cell system, increasing the resistance to apoptosis of cells in culture under UV ray [62]. Nrf2 can be activated by the sulforane (obtained from broccoli and Brussels sprouts) [8].…”
Section: Skinmentioning
confidence: 99%
“…It has been shown that nuclear factor E2-related factor2 (Nrf2) is involved in the protective effect of Hyp on hepatocytes (22,23). Studies have shown that Nrf2 and its cytoplasmic protein, kelch-like ECH-associated protein 1 (Keap1), are central regulators of cell antioxidant responses (24,25). Nrf2 regulates the expression of antioxidant proteins and phase II detoxification enzymes by interacting with a cis-acting transcriptional regulatory element, designated as antioxidant response element or electrophile response element (EpRE).…”
Section: Introductionmentioning
confidence: 99%